2022
DOI: 10.1097/qai.0000000000002912
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Tolerability of Once Daily Coformulated Bictegravir, Emtricitabine, and Tenofovir Alafenamide for Postexposure Prophylaxis After Sexual Exposure

Abstract: Background: Antiretroviral post-exposure prophylaxis (PEP) is recommended to prevent HIV infection after a high-risk exposure, but current regimens have presented challenges in tolerability, regimen completion, and potential drug-drug interactions. Because coformulated bictegravir, emtricitabine, and tenofovir alafenamide [BIC/FTC/tenofovir alafenamide (TAF)] is effective for HIV treatment, it was evaluated for use for PEP.Setting: Boston community health center.Methods: Individuals accessing PEP were enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 42 publications
0
11
0
1
Order By: Relevance
“…From a policy perspective, the regularly changing world of new antiretrovirals presents opportunities for forensic nurses to collaborate with local, state, and federal policy makers to more regularly and rapidly update guidelines to provide post-sexual-assault patients access to the most tolerable medications. As one recent study noted, a once-a-day multidrug formulation for HIV PEP was more tolerable from both a side effect standpoint and was successfully completed by more patients than other regimens (Mayer et al, 2022). Malinverni et al (2021) also report overall higher adherence to HIV PEP with a single-tablet multiformulation, although lower rates of adherence are reported in those exposed via a sexual assault.…”
Section: Discussionmentioning
confidence: 99%
“…From a policy perspective, the regularly changing world of new antiretrovirals presents opportunities for forensic nurses to collaborate with local, state, and federal policy makers to more regularly and rapidly update guidelines to provide post-sexual-assault patients access to the most tolerable medications. As one recent study noted, a once-a-day multidrug formulation for HIV PEP was more tolerable from both a side effect standpoint and was successfully completed by more patients than other regimens (Mayer et al, 2022). Malinverni et al (2021) also report overall higher adherence to HIV PEP with a single-tablet multiformulation, although lower rates of adherence are reported in those exposed via a sexual assault.…”
Section: Discussionmentioning
confidence: 99%
“…The STR bictegravir/FTC/TAF (BIC/FTC/TAF) may represent the best of all these options as it is well‐tolerated, has minimal drug interactions, and a high barrier to resistance. The potential efficacy of BIC/FTC/TAF for PEP was first demonstrated in animal studies, and results from a single‐center study confirmed its overall safety and tolerability 99 . The authors noted, however, that several thousands of patients would be required to have a sufficient event rate to evaluate the efficacy of one PEP regimen against another.…”
Section: Post‐exposure Prophylaxismentioning
confidence: 96%
“…The potential efficacy of BIC/FTC/ TAF for PEP was first demonstrated in animal studies, and results from a single-center study confirmed its overall safety and tolerability. 99 The authors noted, however, that several thousands of patients would be required to have a sufficient event rate to evaluate the efficacy of one PEP regimen against another. The data to support expansion of these newer treatment agents to PEP have increased over time and select STRs have already been incorporated into treatment guidelines in other countries.…”
Section: Updated Pep Regimensmentioning
confidence: 99%
“…17 BIC/TAF/FTC has been shown to be safe and tolerable for PEP. 18 Its use for this indication is supported by expert opinion, 19 as it requires enrollment in only 1 patient assistance program and affords the convenience of a single-tablet regimen to optimize PEP adherence. 15 Patients prescribed 2-drug prophylactic therapy (whether with PrEP or with 2-drug PEP when this was the standard of care at SFCC before May 2016) are asked to stop their prophylactic therapy and offered immediate linkage to HIV care at the time of results disclosure if they test positive for HIV.…”
Section: Study Setting and Designmentioning
confidence: 99%